Three-dimensional analysis of facial morphology in Brazilian population with Caucasian, Asian, and Black ethnicity - Ana Maria Bettoni Rodrigues da Silva; Laís Valencise Magri; Lilian Mendes Andrade; Marco Antônio Moreira Rodrigues da Silva (Wolters Kluwer Medknow Publications, 2017)
Aim: To compare facial features related to the nose, lips and face between the Caucasian, Asian, and Black ethnicity in the Brazilian population by means of linear measurements and proportion indices obtained from the analysis of three-dimensional (3D) images taken by 3D stereophotogrammetry. Materials and Methods: Thirty healthy subjects, being 10 Caucasians, 10 Blacks and 10 Asians had reference points (landmarks) demarcated on their faces, 3D images were obtained (Vectra M3) and the following measurements were calculated: Facial proportion indices relative to the nose, lips and face. The statistical analysis was performed comparing the ethnic groups (one-way analysis of variance). Results: The Blacks and Asians showed the greatest difference in the face analysis (width, height of the lower face, upper face index and lower face index - P < 0.05). In the comparisons between groups, differences were verified to the mouth width and lower lip vermilion height. In the nose analysis, the biggest differences were obtained for the proportion indices, being that Caucasians versus Asians and Caucasians versus Blacks have showed the largest differences. Conclusion: This study found the presence of some similarities in the proportion indices of nose, lips and face between the ethnic groups of the Brazilian population, as well as some important differences that should be known to guide surgical and forensics procedures, among others.